Digital Marketing as A Strategy to Increase Sales and Consumer Satisfaction - Mayhilda Nitami; Rina Novi Yani; Firdaus; Dimas Bagus Susanto; Banta Diman; Nahya Fadillah; Riza Aprillia; Ida Fujari (STMIK Indonesia Banda Aceh, 2024)
The objective of this paper is to conduct a conceptual review of the literature studies that focus on the link between application-based digital marketing methods and the development of consumer satisfaction and sales. The study's findings indicate that digital marketing is a marketing strategy that capitalizes on the advancement of information and digital technology. Implementing this strategy in a business must consider various internal and external factors to determine the suitability and most appropriate digital marketing strategy for maximum results according to the set objectives. Online systems are not constrained by time, and they have the ability to determine the timing, audience, location, and duration of their marketing campaigns. This presents a significant opportunity for business growth. Digital marketing provides a plethora of engaging, practical, and limitless content, and digital technology enables business owners to quantify the impact of their content on sales. Additionally, business owners have the ability to visit an unlimited number of online platforms, such as social media, web pages, and other accounts, which can attract loyal customers and increase profits. This paper reviews conceptually based on literature studies on the relationship between application-based digital marketing strategies in expanding sales and customer satisfaction. For further research, we can examine the efficiency of implementing digital marketing strategies and the factors that influence them so that they can be input and recommendations for business actors or companies in implementing digital-based and internet-connected marketing systems so that they can increase consumer satisfaction.